Water-absorbing material and method for producing water-absorbing material

CN122826045APending Publication Date: 2026-09-25NIPPON SHOKUBAI CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202580017553.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-02-29
Filing Date
2025-02-28
Publication Date
2026-09-25

AI Technical Summary

Benefits of technology

[0026]本发明的一个实施方式的吸水材料与以往的吸水材料相比能够减少使用者的皮肤粗糙等,并且吸水速度和析水率这两者优异。另外,本发明的一个实施方式的吸水材料的制造方法起到能够制造所述吸水材料的效果。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present application provides a water-absorbing material having a continuous skeleton formed of a crosslinked polymer in which a structural unit derived from a (meth)acrylic acid (salt) is a main component, and continuous voids, a centrifuge retention capacity (CRC) of 5 to 25 g / g, a bulk specific gravity of less than 0.3 g / ml, and a neutralization rate of the crosslinked polymer of less than 70 mol%. The water-absorbing material can reduce roughness of the user's skin and the like, and is excellent in water-absorbing speed and water release rate, as compared with conventional water-absorbing materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to an absorbent material and a method for manufacturing the absorbent material. Background Technology

[0002] Currently, in sanitary materials such as diapers, sanitary napkins, and incontinence pads, a mixture of hydrophilic fibers, including absorbent resins and pulp, is widely used as a constituent material to absorb bodily fluids. On the other hand, in recent years, to further improve the absorbency of sanitary materials, technological development is underway to use absorbent materials with superior absorption speeds as constituent materials.

[0003] Here, the absorbent material, for example, is a monolithic organic porous ion exchanger (absorbent material) described in Patent Document 1, which consists of a continuous framework and continuous pores. It should be noted that the monolithic organic porous ion exchanger is a hydrolysate manufactured by hydrolyzing a crosslinked polymer of (meth)acrylate with a compound having two or more vinyl groups in one molecule.

[0004] In addition, as a water-absorbing material consisting of a continuous skeleton and continuous pores, manufactured by methods other than the aforementioned hydrolysis, for example, the water-absorbing polymer particles described in Patent Document 2 are also available. Specifically, these water-absorbing polymer particles are manufactured by a method comprising the following steps (a) and (b).

[0005] (a) The process of encapsulating a first solvent in an aqueous solution of a water-soluble olefinic unsaturated monomer in the presence of a first surfactant to obtain an O / W emulsion.

[0006] (b) The process of dispersing the O / W emulsion obtained in step (a) in a second solvent containing a second surfactant to obtain an O / W / O emulsion.

[0007] Existing technical documents

[0008] Patent documents

[0009] Patent Document 1: Japanese Patent Application Publication No. 2021-007900

[0010] Patent Document 2: Japanese Patent Application Publication No. 2006-342306 Summary of the Invention

[0011] The problem that the invention aims to solve

[0012] On the other hand, the monolithic organic porous ion exchanger described in Patent Document 1 is a hydrolysate, and an excessive amount of alkali is used during its manufacture, neutralizing (meth)acrylic acid, a constituent component, by this alkali. Therefore, even after washing, the alkali remains within the pores of this monolithic organic porous ion exchanger. Consequently, the pH value of this monolithic organic porous ion exchanger exceeds 8, which could contribute to, for example, rough skin in the user.

[0013] Furthermore, the absorbent polymer particles described in Patent Document 2 have room for improvement in terms of water absorption speed. In addition, for absorbent materials that can be used as constituent materials of sanitary materials, excellent water absorption speed and excellent water release rate are also required. Here, excellent water release rate means that when pressure is applied to the absorbent material, which has absorbed aqueous liquid and formed a swollen state, the absorbed aqueous liquid is more easily released and a greater amount is released.

[0014] One embodiment of the present invention aims to solve the aforementioned problems and provide an absorbent material that, compared with conventional absorbent materials, can reduce skin roughness and has excellent absorbency and water release rate.

[0015] Solution for solving the problem

[0016] The inventors have discovered that the following absorbent material can solve the aforementioned problem: an organic porous body formed from a crosslinked polymer with a neutralization rate lower than that of conventional absorbent materials, and containing an organic porous body with a specific porous structure having a water retention capacity and a bulk density within a specific range. Furthermore, the inventors have discovered that in the manufacturing method described in Patent Document 2, by controlling the volume ratio (O / W volume ratio) of the first solvent to the unsaturated monomer aqueous solution to 2.5 or more, an absorbent material containing an organic porous body with the aforementioned specific porous structure can be obtained.

[0017] That is, one embodiment of the present invention is a water-absorbing material comprising an organic porous body having a continuous framework formed by a cross-linked polymer whose main components are structural units derived from (meth)acrylate (salt), and continuous pores.

[0018] The centrifugal retention capacity (CRC) of this absorbent material is 5–25 g / g.

[0019] The bulk density is less than 0.3 g / ml, and,

[0020] The neutralization rate of the crosslinked polymer is less than 70 mol%.

[0021] Another embodiment of the present invention is a method for manufacturing a water-absorbing material, the water-absorbing material comprising an organic porous body having a continuous framework formed by a cross-linked polymer with structural units derived from (meth)acrylate (salt) as the main component, and continuous pores, the manufacturing method comprising:

[0022] In the O / W emulsion preparation process, in a monomer aqueous solution with a neutralization rate of less than 70 mol%, a first solvent is encapsulated therein in the presence of a first surfactant, such that the volume ratio of the first solvent to the monomer aqueous solution is 2.5 or more, thereby obtaining an O / W emulsion.

[0023] The O / W / O emulsion preparation process involves dispersing the O / W emulsion in a second solvent to obtain an O / W / O emulsion; and

[0024] In the polymerization process, monomers contained in the monomer aqueous solution are polymerized in the O / W / O emulsion to prepare an organic porous body.

[0025] Invention Effects

[0026] The absorbent material of one embodiment of the present invention can reduce skin roughness and other issues compared to conventional absorbent materials, and it also exhibits superior absorption speed and water release rate. Furthermore, the manufacturing method of the absorbent material of one embodiment of the present invention enables the production of the aforementioned absorbent material. Attached Figure Description

[0027] Figure 1 This is a schematic diagram illustrating one embodiment of the O / W / O emulsion preparation and polymerization process of a method for manufacturing an absorbent material according to an invention. Detailed Implementation

[0028] The following describes one embodiment of the present invention, but the present invention is not limited thereto. The present invention is not limited to the configurations described below, and various modifications can be made within the scope shown in the claims. Embodiments obtained by appropriately combining the technical means disclosed in different embodiments are also included within the technical scope of the present invention. It should be noted that, unless otherwise specified, in this specification, "A to B" indicating a numerical range means "A or more and B or less".

[0029] [1. Definition of the term]

[0030] [1-1. Crosslinked polymers]

[0031] In this specification, “crosslinked polymer” specifically refers to a polymer gelling agent with a water swelling (CRC) of 5 g / g or more as specified in NWSP 241.0.R2 (15) and a water soluble content (Ext) of 70% by mass or less as specified in NWSP 270.0.R2 (15).

[0032] It should be noted that "NWSP" stands for "Non-Woven Standard Procedures-Edition 2015". NWSP is a standard jointly issued by EDANA (European Disposables and Nonwovens Association) and INDA (Association of the Nonwoven Fabrics Industry) in the United States and Europe to standardize the evaluation methods for nonwoven fabrics and their products, including standard methods for determining the properties of absorbent polymers. Unless otherwise specified, the properties of crosslinked polymers and absorbent materials in this specification are determined according to NWSP.

[0033] In this specification, "crosslinked polymer" is not limited to a composition in which the total amount (100% by mass) is solely that crosslinked polymer, but can also be a composition that includes additives, etc., and is commonly referred to as a "water-absorbing resin composition". Furthermore, in this specification, "crosslinked polymer" can refer to a crosslinked polymer in a state where water has been incorporated into it as a hydrogel.

[0034] [1-2. Absorbent Material]

[0035] In this specification, "absorbent material" refers to a material having a continuous skeleton and continuous pores formed mainly of a cross-linked polymer, capable of absorbing and retaining solutions (liquids). In particular, it can be used as an absorbent in combination with particulate superabsorbent polymers with excellent water absorption properties, commonly referred to as superabsorbent resins. The absorbent material of the present invention is an absorbent agent characterized by temporarily retaining a liquid and transferring it to the superabsorbent polymer in this application scenario. Here, the solution (liquid) is not limited to water; any liquid is not particularly limited. Liquids absorbed by the absorbent material of one embodiment of the present invention include, for example, urine, menstrual blood, sweat, saline solution, oil, organic solvents, and waste liquid.

[0036] The absorbent material described in this specification can be a granular (powdered) absorbent material, commonly referred to as "granular absorbent material". Since the granular absorbent material contains a cross-linked polymer as its main component, it is equivalent to a granular cross-linked polymer. The concept of "granular absorbent material" includes both single granular absorbent materials and aggregates of multiple granular absorbent materials. In this specification, "granular" refers to having a granular morphology. In this application specification, "granule" refers to a smaller fraction of a substance, having a size of several Å to several mm (see "granule", McGraw-Hill Technical Terminology Dictionary Editorial Committee, 3rd Edition, Nikkan Kogyo Shimbun, 1996, p. 1929). It should be noted that in this specification, "granular absorbent material" is sometimes abbreviated as "absorbent material".

[0037] The absorbent material contains a cross-linked polymer (or particulate cross-linked polymer) as its main component. The absorbent material contains 60–100% by mass, preferably 70–95% by mass, and more preferably 75–90% by mass of the cross-linked polymer. The remaining portion of the absorbent material may optionally contain water and / or additives (inorganic microparticles, polyvalent metal cations, etc.).

[0038] That is, the upper limit of the cross-linked polymer in the absorbent material is, for example, 100% by mass, 90% by mass, 80% by mass, or 70% by mass. Moreover, it is preferable that in addition to the cross-linked polymer, it also contains 5 to 30% by mass of components, especially water and / or additives (inorganic microparticles, polyvalent metal cations, etc.).

[0039] It should be noted that the preferred moisture content of the absorbent material is 0.2 to 30% by mass. As mentioned above, compositions containing water and / or additives integrated with and / or mixed with crosslinked polymers are also included in "particulate absorbent materials". The "moisture content" in this specification is a numerical value representing the proportion of the mass of water contained in the test object to the total mass of the test object, or more specifically, the total mass of the test object in a water-containing state, and can be calculated based on the following formula (2). Examples of the test objects include the absorbent material, the organic porous body described later, the crosslinked polymer described later, and the hydrogel described later, and the moisture content can be calculated in the same way.

[0040] [Moisture content (mass%) of the test object] = [(mass of water in the test object) ÷ (mass of the test object as a whole)] × 100… (2)

[0041] [2. Absorbent Material]

[0042] The absorbent material of one embodiment of the present invention (hereinafter referred to as "the absorbent material of the present invention") is an absorbent material comprising an organic porous body having a continuous skeleton formed by a cross-linked polymer with structural units derived from (meth)acrylate (salt) as the main component, and continuous pores. The absorbent material has a centrifuge holding capacity (CRC) of 5 to 25 g / g, a bulk density of less than 0.3 g / ml, and a neutralization rate of less than 70 mol of the cross-linked polymer.

[0043] In the absorbent material of the present invention, the neutralization rate of the crosslinked polymer is less than 70 mol%. Therefore, the absorbent material of the present invention is controlled to be weakly acidic, and for example, compared with conventional absorbent materials, it can reduce skin roughness of the user.

[0044] The absorbent material of the present invention contains an organic porous body having a continuous skeleton formed by a cross-linked polymer and continuous pores, so that when absorbing liquids such as water, the liquid is retained inside the cross-linked polymer and the continuous pores.

[0045] Furthermore, the CRC refers to the amount of liquid remaining in the absorbent material after a portion of the liquid is released when a specific centrifugal force (pressure) is applied to the swollen absorbent material that has absorbed the liquid. When the centrifugal force is applied, the liquid primarily contained within the continuous pores is released from the swollen absorbent material. Therefore, the CRC mainly refers to the amount of liquid remaining in the crosslinked polymer of the swollen absorbent material.

[0046] The bulk density is a parameter representing the mass per unit volume of the absorbent material. This mass primarily refers to the mass of the cross-linked polymer constituting each unit volume of the absorbent material. Therefore, the bulk density is a parameter representing the ratio of the portion occupied by the continuous skeleton to the portion occupied by the continuous pores in the overall absorbent material. That is, a lower bulk density indicates that the continuous skeleton occupies a smaller portion and the continuous pores occupy a larger portion in the overall absorbent material.

[0047] The absorbent material of the present invention has a CRC of less than 25 g / g and a bulk density controlled to be less than 0.3 g / ml. Therefore, the absorbent material of the present invention has a structure in which the continuous pores occupy a large portion. This structure makes it easier to draw the liquid into its interior and to release the liquid more easily when centrifugal force (pressure) is applied. Therefore, the absorbent material of the present invention exhibits excellent water absorption rate and water release rate.

[0048] The absorbent material of the present invention has a CRC of 5 g / g or more. This means that the absorbent material of the present invention comprises a portion occupied by the continuous skeleton in a predetermined amount. Therefore, the absorbent material of the present invention has the specified absorbent properties.

[0049] As a result, compared with conventional absorbent materials, the absorbent material of the present invention can reduce skin roughness and other issues for users, and both its absorption speed and water release rate are excellent.

[0050] It should be noted that Patent Document 2 describes the insufficient mechanical strength of absorbent materials containing organic porous bodies with low bulk density. On the other hand, for the absorbent material of the present invention, its mechanical strength was confirmed by a method of adding the absorbent material and glass beads to a glass container and then vibrating it (damage test). The results confirmed that the absorbent material of the present invention possesses sufficient mechanical strength to be used as an absorbent material. It should be noted that this method simulates mechanical damage applied during manufacturing processes in chemical plants, etc.

[0051] The following is a detailed description of the components constituting the absorbent material of the present invention and the characteristics of the absorbent material of the present invention.

[0052] [2-1. Crosslinked polymers]

[0053] The water-absorbing material of the present invention has a cross-linked polymer whose main component is a structural unit derived from (meth)acrylate (salt). More specifically, the cross-linked polymer is a hydrophilic cross-linked polymer, i.e., a poly(meth)acrylate (acid) cross-linked polymer, formed by cross-linking and polymerizing a monomer composition containing (meth)acrylate (salt) monomers.

[0054] In this specification, "(meth)acrylic acid (salt)" refers to (meth)acrylic acid and / or its salts. Additionally, "monomer composition containing (meth)acrylic acid (salt) monomers" refers to a monomer composition containing 50 mol% or more (meth)acrylic acid (salt) relative to all monomers except crosslinking agents.

[0055] The water-absorbing material of the present invention has a crosslinked polymer that comprises more than 50 mol% of structural units derived from (meth)acrylate (salt) relative to the total structural units constituting the poly(meth)acrylate (salt) crosslinked polymer, and is a crosslinked polymer having structural units derived from an internal crosslinking agent as any component.

[0056] The crosslinked polymer is a crosslinked polymer in which 50 mol% or more, preferably 70 mol% or more, and more preferably 90 mol% or more of (meth)acrylate (salt) is present in the monomers constituting the product, excluding the internal crosslinking agent. Alternatively, the crosslinked polymer is a crosslinked polymer in which 100 mol% or less, and more preferably substantially 100 mol% of (meth)acrylate (salt) is present in the monomers constituting the product, excluding the internal crosslinking agent.

[0057] The cross-linked polymer in the absorbent material of the present invention can be, for example, granular. The granular cross-linked polymer can have one or more shapes selected from the group consisting of amorphous, fragmented, spherical, fibrous, rod-shaped, substantially spherical, and flattened forms. Preferably, at least a portion of the cross-linked polymer is spherical particles. Considering damage during the manufacturing process, from the viewpoint of reduced productivity due to the generation of micropowder, the cross-linked polymer is more preferably spherical. The granular cross-linked polymer is referred to as a granular cross-linked polymer whether it is a single particle or an aggregate of multiple particles. Furthermore, the cross-linked polymer is porous.

[0058] <Monomers, Monomer Compositions>

[0059] In this specification, "monomer composition" refers to the raw material components that form the crosslinked polymer. It refers to a composition that, in addition to (meth)acrylate (salt) as the main monomer component, includes monomers other than (meth)acrylate (salt) and an internal crosslinking agent as an optional component. That is, the raw material components constituting the crosslinked polymer are referred to as monomer composition.

[0060] As monomers other than the aforementioned (meth)acrylic acid (salt), monomers containing acid groups are preferred among monomers having unsaturated double bonds (olefinic unsaturated monomers). Specifically, examples of such monomers include: maleic acid (anhydride), fumaric acid, crotonic acid, itaconic acid, cinnamic acid, vinyl sulfonic acid, allyl toluenesulfonic acid, vinyl toluenesulfonic acid, styrene sulfonic acid, 2-(meth)acrylamide-2-methylpropanesulfonic acid, 2-(meth)acryloylethanesulfonic acid, 2-(meth)acryloylpropanesulfonic acid, and 2-hydroxyethyl(meth)acryloyl phosphate, and / or their salts. One or more of these monomers may be used as needed.

[0061] The salt can be one or more salts selected from the group consisting of alkali metal salts, ammonium salts and amine salts, more preferably sodium salts, potassium salts, lithium salts or ammonium salts, and particularly preferably sodium salts.

[0062] Furthermore, the neutralization rate of the crosslinked polymer in the absorbent material of the present invention can be controlled by the neutralization rate of the monomer composition. Alternatively, a neutralizing agent can be added to the crosslinked polymer or the absorbent material after the polymerization process for adjustment. The neutralization rate is the ratio (in moles %) of the number of neutralized monomers to the number of moles of all monomers constituting the crosslinked polymer (excluding internal crosslinking agents).

[0063] The absorbent material of the present invention has a neutralization rate of less than 70 mol%, which is a relatively small value. As mentioned above, compared with conventional absorbent materials, it can reduce skin roughness and other issues for the user. From this point of view, the neutralization rate is preferably 65 mol% or less.

[0064] Furthermore, by achieving a neutralization rate of at least a predetermined value, the water absorption properties of the absorbent material of the present invention, such as the water absorption ratio and water absorption speed, can be improved. From this perspective, the neutralization rate is preferably 30 mol% or more, and more preferably 40 mol% or more.

[0065] In addition, the monomer composition may, as needed, contain hydrophilic or hydrophobic unsaturated monomers (hereinafter referred to as "other monomers"), in addition to the aforementioned "(meth)acrylate (salt)" and "monomers other than (meth)acrylate (salt)".

[0066] Other monomers include, for example, unsaturated monomers containing thiol groups; unsaturated monomers containing phenolic hydroxyl groups; unsaturated monomers containing amide groups such as N-vinyl-2-pyrrolidone, N-vinylacetamide, (meth)acrylamide, N-isopropyl (meth)acrylamide, N-ethyl (meth)acrylamide, and N,N-dimethyl (meth)acrylamide; and unsaturated monomers containing amino groups such as N,N-dimethylaminoethyl (meth)acrylate, N,N-dimethylaminopropyl (meth)acrylate, and N,N-dimethylaminopropyl (meth)acrylamide. More than one of these other monomers may be used.

[0067] Regarding the amount of other monomers, it is acceptable as long as it does not impair the physical properties of the obtained absorbent material. Specifically, it is 50 mol% or less, more preferably 20 mol% or less, relative to the portion of the monomer composition excluding the internal crosslinking agent.

[0068] <Internal cross-linking agent>

[0069] The crosslinked polymer is crosslinked. The crosslinking can be a self-crosslinking type without the use of crosslinking monomers. Alternatively, from a physical property perspective, the crosslinked polymer is preferably internally crosslinked using an internal crosslinking agent.

[0070] The internal crosslinking agent is preferably selected from at least one of the group consisting of multifunctional acrylate crosslinking agents, acrylamide crosslinking agents, and glycidyl ether crosslinking agents.

[0071] Specifically, examples of internal crosslinking agents include: N,N'-methylenebis(meth)acrylamide, polyethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, trimethylolpropane di(meth)acrylate, trimethylolpropane tri(meth)acrylate, glycerol tri(meth)acrylate, glycerol acrylate methacrylate, ethylene oxide modified trimethylolpropane tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, triallyl cyanurate, triallyl isocyanurate, triallyl phosphate, triallylamine, poly(meth)allyloxyalkylene, polyethylene glycol diglycidyl ether, glycerol diglycidyl ether, ethylene glycol, polyethylene glycol, propylene glycol, glycerol, pentaerythritol, ethylenediamine, polyethyleneimine, and glycidyl (meth)acrylate, etc. From these internal crosslinking agents, at least one internal crosslinking agent is selected, taking into account factors such as reactivity.

[0072] In this invention, from the viewpoint of the water absorption properties of the crosslinked polymer and the water-absorbing material of this invention, it is preferable to select an internal crosslinking agent having two or more polymerizable unsaturated groups.

[0073] Specifically, allyl and (meth)acrylate groups can be listed as polymerizable unsaturated groups. Among these, (meth)acrylate groups are preferred. An internal crosslinking agent having two or more polymerizable unsaturated groups possessing a (poly)alkylene glycol structure can be used; for example, polyethylene glycol di(meth)acrylate can be listed. It should be noted that the number of alkylene glycol units in this internal crosslinking agent is preferably 1 or more, more preferably 2 or more, further preferably 4 or more, and particularly preferably 6 or more. Furthermore, the number of alkylene glycol units is preferably 100 or less, more preferably 50 or less, further preferably 20 or less, and particularly preferably 10 or less.

[0074] The content of the internal crosslinking agent relative to the portion of the monomer composition excluding the internal crosslinking agent is preferably 0.001 mol% or more, more preferably 0.01 mol% or more, and even more preferably 0.1 mol% or more. Furthermore, the content of the internal crosslinking agent relative to the portion of the monomer composition excluding the internal crosslinking agent is preferably 10 mol% or less, more preferably 7 mol% or less, and even more preferably 5 mol% or less.

[0075] When the content of the internal crosslinking agent is within the specified range, the water absorption properties of the crosslinked polymer and the absorbent material of the present invention can be controlled within a desired range. On the other hand, when the content of the internal crosslinking agent is outside the specified range, as the gel strength of the crosslinked polymer decreases, the water-soluble component of the crosslinked polymer increases, or the absorption rate of the crosslinked polymer and the absorbent material of the present invention decreases.

[0076] <Surface Crosslinking Agent>

[0077] The crosslinked polymer can be surface-crosslinked and has a surface-crosslinked layer. This surface-crosslinked layer can be formed on the surface of the crosslinked polymer, for example, by surface crosslinking using a surface crosslinking agent as described in U.S. Patent No. 7,183,456. Among these surface crosslinking agents, at least one is selected considering reactivity and other factors. Furthermore, from the viewpoint of the operability of the surface crosslinking agent and the water absorption performance of the absorbent material, an organic compound having two or more functional groups that react with carboxyl groups and form covalent bonds is preferred.

[0078] Examples of surface crosslinking agents include: ethylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, polyethylene glycol, propylene glycol, dipropylene glycol, polypropylene glycol, 1,3-propanediol, 1,2-butanediol, 1,3-butanediol, 1,4-butanediol, 2,3-butanediol, 1,2-pentanediol, 1,3-pentanediol, 1,4-pentanediol, 1,5-pentanediol, 2,3-pentanediol, 2,4-pentanediol, 1,2-hexanediol, and 1,3-hexanediol. Polyols such as 1,4-hexanediol, 1,5-hexanediol, 1,6-hexanediol, 2,3-hexanediol, 2,4-hexanediol, glycerol, polyglycerol, diethanolamine, and triethanolamine; polyamines such as ethylenediamine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, pentaethylenehexamine, polyallylamine, and polyethyleneimine; halogenated epoxy compounds; condensates of polyamines and halogenated epoxy compounds; and oxazoline compounds such as 1,2-ethylenebisoxazoline. Compounds; oxazolidinone compounds; 1,3-dioxolane-2-one (ethylene carbonate), 4-methyl-1,3-dioxolane-2-one, 4,5-dimethyl-1,3-dioxolane-2-one, 4,4-dimethyl-1,3-dioxolane-2-one, 4-ethyl-1,3-dioxolane-2-one, 4-hydroxymethyl-1,3-dioxolane-2-one, 1,3-dioxane-2-one, 4-methyl-1,3-dioxane-2-one, Alkyl carbonate esters such as 4,6-dimethyl-1,3-dioxane-2-one and 1,3-dioxane-heptane-2-one; polyglycidyl compounds such as ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, glycerol polyglycidyl ether, diglycerol polyglycidyl ether, polyglycerol polyglycidyl ether, and glycidyl; oxetane compounds; vinyl ether compounds; cyclic urea compounds; etc. One of these compounds may be used alone or in combination of two or more.

[0079] [2-2. Organic Porous Materials]

[0080] The organic porous body of the present invention has a continuous framework formed by the cross-linked polymer and continuous pores. In other words, the organic porous body is an organic porous body formed by the cross-linked polymer, and its shape can be granular. Therefore, the organic porous body can be the granular cross-linked polymer.

[0081] The thickness of the continuous skeleton of the organic porous body in its dry state is preferably 0.1 μm or more, more preferably 0.5 μm or more, and even more preferably 1 μm or more. When the thickness is at or above the lower limit value, the strength of the organic porous body and the absorbent material of the present invention can be improved.

[0082] Furthermore, the thickness is preferably 100 μm or less, more preferably 50 μm or less, and even more preferably 10 μm or less. When the thickness is below the aforementioned upper limit, the rate at which the absorbent material of the present invention absorbs liquids such as water can be increased.

[0083] It should be noted that, regarding the determination of the thickness of the continuous framework of the organic porous body in its dry state, since the pore structure of the organic porous body is a continuous bubble structure, the cross-section of the framework appearing on the test piece used for electron microscopy measurement of the absorbent material of the present invention is used as the evaluation area for thickness. The continuous bubble structure refers to a structure in which large bubble-like pores overlap each other.

[0084] The average diameter of the continuous pores in the dry state of the organic porous body is preferably 0.1 μm or more, more preferably 1.0 μm or more, and even more preferably 2.0 μm or more. When the average diameter is at or above the lower limit value, the rate at which the absorbent material of the present invention absorbs liquids such as water can be improved.

[0085] Furthermore, the average diameter of the continuous pores in the dry state of the organic porous body is preferably 1000 μm or less, more preferably 100 μm or less, and even more preferably 50 μm or less. When the average diameter is below the upper limit value, the strength of the organic porous body and the absorbent material of the present invention can be improved.

[0086] The sample used to measure the thickness of the continuous skeleton and the average diameter of the continuous pores was a sample obtained by drying the absorbent material of the present invention at 50°C for more than 18 hours using a vacuum dryer. At this time, the final pressure was set to 0 Torr.

[0087] [2-3. Surfactants]

[0088] The absorbent material of the present invention can be manufactured by a method for manufacturing absorbent materials according to one embodiment of the present invention, described later. Therefore, due to surfactant residues used in this manufacturing method, it will contain surfactants.

[0089] The surfactant may be, for example, one of the surfactants listed as "first surfactant" and "second surfactant" described later as specific examples. The surfactant may be one type or a mixture of two or more types.

[0090] Regarding the upper limit of the surfactant content, it is preferably 15 parts by weight or less, more preferably 10 parts by weight or less, relative to 100 parts by weight of the crosslinked polymer. When the upper limit of the surfactant content is below this value, the reduction in water absorption performance caused by the surfactant remaining in the absorbent material of the present invention can be prevented, and water absorption performance such as absorption speed can be improved. The lower limit of the surfactant content is not particularly limited; for example, it can be 0.045 parts by weight or more, preferably 0.090 parts by weight or more, relative to 100 parts by weight of the crosslinked polymer.

[0091] [2-4. Chelating agents]

[0092] The absorbent material of the present invention may contain a chelating agent. The chelating agent may be, for example, a polycarboxylic acid or its salt. Preferably, the chelating agent has a high ion-blocking and chelating ability for Fe or Cu. Specifically, the chelating agent is one with a stability constant for Fe ions of 10 or more, preferably 20 or more, and more preferably an aminopolycarboxylic acid or its salt. The aminopolycarboxylic acid or its salt may be a polymer. As the aminopolycarboxylic acid or its salt, it is particularly preferred that the lower limit of the number of carboxyl groups is 3 or more, preferably 4 or more, more preferably 5 or more, and the upper limit is generally 100 or less, more preferably 20 or less.

[0093] Examples of the polycarboxylic acids include diethylenetriaminepentaacetic acid, triethylenetetraminehexaacetic acid, cyclohexane-1,2-diaminetetraacetic acid, N-hydroxyethylethylenediaminetriacetic acid, ethylene glycol diethyl ether diaminetetraacetic acid, ethylenediaminetetrapropionic acid, N-alkyl-N'-carboxymethyl aspartic acid, and N-alkenyl-N'-carboxymethyl aspartic acid, as well as their alkali metal salts, alkaline earth metal salts, ammonium salts, and amine salts. Among these polycarboxylic acids, diethylenetriaminepentaacetic acid, triethylenetetraminehexaacetic acid, N-hydroxyethylethylenediaminetriacetic acid, and their salts are most preferred. More than one of the polycarboxylic acids may be used.

[0094] The chelating agent, particularly the amino polycarboxylic acid, is present in trace amounts relative to 100 parts by weight of the crosslinked polymer, typically 0.00001 to 10 parts by weight, preferably 0.0001 to 1 part by weight, and more preferably 0.01 to 0.5 parts by weight.

[0095] At this point, the full effect and / or additional functions brought about by the chelating agent can be obtained, while maintaining the absorbency of the absorbent material.

[0096] [2-5. Inorganic particles]

[0097] To prevent sticking during moisture absorption, the absorbent material of the present invention may contain inorganic microparticles, particularly water-insoluble inorganic microparticles. Examples of such inorganic microparticles include one or more selected from the group consisting of metal oxides such as silica and titanium dioxide, silica (salts) such as natural and synthetic zeolites, kaolin, talc, clay, and bentonite. Among these inorganic microparticles, silica and silica (salts) are more preferred, and silica and silica (salts) with an average particle size of 0.001 to 200 μm as determined by the Coulter counting method are even more preferred. Furthermore, the absorbent material of the present invention can be given deodorizing properties by containing zeolite, with zeolite having a SiO2:Al2O3 ratio of 1:1 to 100, preferably 1:2 to 10, being preferred.

[0098] Regarding the content of the inorganic microparticles, it is generally 0 to 10 parts by mass relative to 100 parts by mass of the crosslinked polymer, preferably 0.001 to 5 parts by mass, and more preferably 0.002 to 3 parts by mass.

[0099] At this point, the full effects and / or additional functions resulting from the presence of inorganic microparticles can be obtained, while maintaining the absorbency of the absorbent material.

[0100] [2-6. Other additives]

[0101] The absorbent material of the present invention may contain other additives besides the surfactant, the chelating agent and the inorganic microparticles, without prejudice to the purpose of the present invention.

[0102] Other additives mentioned above may include plant components, polyvalent metal salts of organic acids, complex hydrated oxides, reducing substances, antibacterial agents, deodorants, water-soluble polymers, water-insoluble polymers, water, organic microparticles, reducing agents, oxidizing agents, and inorganic salts.

[0103] The content of the other additives can vary depending on the purpose and additional functions. For example, typically, the content of each additive is 0 parts by weight or more and 10 parts by weight or less relative to 100 parts by weight of the crosslinked polymer, preferably 0.001 parts by weight or more and 5 parts by weight or less, and more preferably 0.002 parts by weight or more and 3 parts by weight or less. More than one additive may be used.

[0104] At this point, the full effect and / or additional functions brought about by the additives can be obtained, while maintaining the absorbency of the absorbent material.

[0105] [2-7. Physical properties of absorbent materials]

[0106] <Centrifuge Retention Capacity (CRC) (NWSP241.0.R2(15))>

[0107] CRC is usually short for Centrifuge Retention Capacity, a parameter known as the water absorption ratio without pressure.

[0108] Specifically, the CRC refers to the water absorption ratio (unit: g / g) after placing 0.2g of the absorbent material into a nonwoven bag, immersing it in a large excess of 0.9% (w / w) sodium chloride aqueous solution for 30 minutes to allow it to swell freely, and then controlling the water using a centrifuge (250G). The CRC can be determined, for example, by the method shown in the embodiment.

[0109] The CRC of the absorbent material of the present invention is 25 g / g or less, preferably 23 g / g or less, and more preferably 20 g / g or less.

[0110] Furthermore, the CRC is 5 g / g or more, preferably 7 g / g or more, and more preferably 10 g / g or more. From the viewpoint of maintaining the water absorption performance, such as the water absorption rate, of the absorbent material of the present invention, it is preferable that the CRC is at or above the lower limit value. The value of the CRC can be controlled by changing the type and amount of the internal crosslinking agent and the surface crosslinking agent, thereby adjusting the water absorption capacity of the crosslinked polymer.

[0111] Bulk density

[0112] The bulk density of the absorbent material of the present invention is a parameter representing the mass per unit volume. The bulk density is the mass of the absorbent material when it is allowed to fall freely and fill a 10 mL container (unit: [g / mL]).

[0113] The bulk density is less than 0.3 g / mL, preferably less than 0.27 g / mL, more preferably less than 0.25 g / mL, even more preferably less than 0.20 g / mL, and still more preferably less than 0.17 g / mL. When the bulk density is below the upper limit, as mentioned above, the absorbent material of the present invention has a structure with large and / or numerous continuous pores, resulting in improved water absorption rate and water separation rate of the absorbent.

[0114] Furthermore, the bulk density is preferably 0.05 g / mL or more, more preferably 0.07 g / mL or more. From the viewpoint of maintaining the absorbent properties such as CRC of the absorbent material of the present invention, the bulk density is preferably at or above the lower limit value.

[0115] <Water absorption rate (Vortex)>

[0116] The water absorption rate of the absorbent material of the present invention is expressed, for example, as a value (absorption rate (Vortex): unit [seconds]) determined by a method commonly known as the Vortex method. A smaller Vortex value indicates a faster and more efficient water absorption. A smaller Vortex value is preferred for the absorbent material of the present invention; specifically, it is preferably 10 seconds or less, more preferably 7 seconds or less, further preferably 5 seconds or less, and particularly preferably 2 seconds or less. The Vortex value can be determined, for example, by the method described in the embodiments.

[0117] <Free Swelling Ratio (FSC) (NWSP 240.0.R2(15))>

[0118] The Free Swell Capacity (FSC) of the absorbent material of the present invention is an abbreviation for Free Swell Capacity, which refers to the water absorption capacity of the absorbent material under suspension without pressure. In this specification, the FSC is measured according to NWSP240.0.R2 (15). The FSC value of the absorbent material can be controlled by changing the type and amount of internal crosslinking agent and surface crosslinking agent, etc., to adjust the water absorption capacity of the crosslinked polymer.

[0119] The FSC value is preferably 35 g / g or more, more preferably 40 g / g or more, and even more preferably 50 g / g or more. Furthermore, the FSC value is preferably 150 g / g or less, more preferably 120 g / g or less, and even more preferably 100 g / g or less. By having the FSC value within this range, the water absorption rate and water separation rate of the absorbent material of the present invention can be further improved.

[0120] <Water Diversion Rate>

[0121] The water release rate of the absorbent material of the present invention is a parameter that indicates the ease with which the liquid is released when a certain pressure (centrifugal force) is applied to the absorbent material in a swollen state after absorbing water or other liquids, and is expressed by the following formula (1).

[0122] Water separation rate [%] = {(FSC[g / g] - CRC[g / g]) / FSC[g / g]} × 100 · · (1)

[0123] A high water separation rate means that the liquid absorbed by the swollen absorbent material is released more easily, resulting in excellent water separation performance. A higher water separation rate is preferred; specifically, it is preferably 40% or higher, more preferably 50% or higher, and even more preferably 60% or higher. Additionally, the water separation rate is typically 95% or lower.

[0124] <ph>

[0125] The pH of the absorbent material of the present invention is controlled within a range exhibiting weak acidity, specifically, within the range of 4.5 to 6.5, and preferably within the range of 5.0 to 6.0. The pH can be controlled by adjusting the neutralization rate of the monomer composition used as a raw material to within this range. The pH can be measured using the method described in the examples.

[0126] <Mass average particle size (D50)>

[0127] The absorbent material of the present invention is a porous material and can be granular. Its mass-average particle size (D50) is preferably 100 μm or more and 1000 μm or less, more preferably 300 μm or more and 800 μm or less, and even more preferably 400 μm or more and 700 μm or less. It should be noted that the mass-average particle size (D50) refers to the particle size of a standard sieve corresponding to 50% by mass of the total particles when using a standard sieve with a certain mesh size, as described in U.S. Patent No. 5051259, etc. The D50 can be measured, for example, by the method described in the embodiments.

[0128] [2-8. Manufacturing method]

[0129] The absorbent material of the present invention can be manufactured, for example, by a method for manufacturing absorbent materials according to one embodiment of the present invention described later.

[0130] [2-9. Uses of absorbent materials]

[0131] The absorbent material of the present invention is an organic porous body having a continuous backbone formed mainly of a cross-linked polymer and continuous pores, thus possessing the ability to absorb and retain solutions (liquids). Therefore, it can be used in absorbents of sanitary materials, etc., and as mentioned above, it can be used in combination with existing superabsorbent polymers with excellent water absorption properties, such as absorbent resins. Furthermore, since the absorbent material of the present invention is a particulate porous body, it can be easily mixed with particulate superabsorbent polymers (absorbent resins) to form a composition for use in absorbents, etc. Such composite absorbents comprising the absorbent material of the present invention and absorbent resin particles are also included in the present invention.

[0132] [3. Manufacturing method of water-absorbing material]

[0133] A method for manufacturing a water-absorbing material according to one embodiment of the present invention (hereinafter referred to as "the manufacturing method of the present invention") is a method for manufacturing a water-absorbing material comprising an organic porous body having a continuous framework formed by a cross-linked polymer with structural units mainly derived from (meth)acrylate (salt) as the main component, and continuous pores. The manufacturing method includes: an O / W emulsion preparation step, wherein a first solvent is encapsulated in a monomer aqueous solution with a neutralization rate of less than 70 mol% in the presence of a first surfactant at a volume ratio of the first solvent to the monomer aqueous solution of 2.5 or more, to obtain an O / W emulsion; an O / W / O emulsion preparation step, wherein the O / W emulsion is dispersed in a second solvent to obtain an O / W / O emulsion; and a polymerization step, wherein the monomer contained in the monomer aqueous solution is polymerized in the O / W / O emulsion to prepare the organic porous body.

[0134] In the manufacturing method of the present invention, the description of "crosslinked polymer", "organic porous body" and "water-absorbing material" can be found in the section [2. water-absorbing material].

[0135] The objective of this invention is to provide a water-absorbing material that, compared to conventional water-absorbing materials, reduces skin roughness and other issues for the user, and exhibits superior water absorption speed and water release rate. The inventors have discovered that the water-retention capacity and bulk density of the water-absorbing material manufactured by the method of this invention are controlled within a specific range, and that the water-absorbing material can solve the aforementioned problems. Furthermore, the inventors have discovered that by making the monomer neutralization rate lower than that of conventional monomers, an O / W emulsion with an O / W volume ratio of 2.5 or higher can be prepared, enabling the manufacture of a water-absorbing material that solves the aforementioned problems. It should be noted that, here, the monomer neutralization rate corresponds to the neutralization rate of the crosslinked polymer constituting the water-absorbing material to be manufactured.

[0136] Here, refer to Figure 1 The present invention will explain the fact that the manufacturing method of the present invention can provide an absorbent material that can solve the aforementioned problems. Figure 1 This is a schematic diagram illustrating one embodiment of the O / W / O emulsion preparation and polymerization process of the manufacturing method of the present invention.

[0137] Figure 1 The diagram on the left shows an O / W emulsion prepared in the O / W emulsion preparation step of the manufacturing method of the present invention. The O / W emulsion is as follows: Figure 1 As shown in the figure on the left, a first solvent 1 is dispersed in a monomer aqueous solution 2, and the volume ratio (O / W volume ratio) of the first solvent 1 to the monomer aqueous solution 2 is 2.5 or more.

[0138] In the O / W / O emulsion preparation step of the manufacturing method of the present invention, such as Figure 1 As shown from the left to the center, the O / W emulsion prepared in the O / W emulsion preparation step is added to the second solvent 3 and emulsified. Thus, an O / W / O emulsion in which the O / W emulsion 4 is dispersed in the second solvent 3 is prepared.

[0139] Here, in O / W emulsion 4, the first solvent is dispersed in the monomer aqueous solution. Furthermore, the O / W volume ratio in O / W emulsion 4 is the same as the O / W volume ratio in the O / W emulsion prepared in the O / W emulsion preparation step described above.

[0140] In the polymerization step of the manufacturing method of the present invention, such as Figure 1 As shown on the right, monomers contained in the aqueous monomer solution of the O / W emulsion 4 polymerize to form a crosslinked polymer. Then, through this crosslinked polymer, a continuous framework constituting the organic porous body 5 prepared by the polymerization process is formed. Furthermore, since no crosslinked polymer is formed in the first solvent dispersed in the O / W emulsion 4, the portion containing this first solvent becomes the continuous pores constituting the organic porous body 5. Therefore, through the polymerization process, as... Figure 1 As shown in the figure on the right, an organic porous body is prepared having a continuous framework formed by a cross-linked polymer and a structure having continuous pores dispersed inside. That is, in the manufacturing method of the present invention, an absorbent material comprising an organic porous body having the aforementioned continuous framework and continuous pores is manufactured. It should be noted that... Figure 1 The organic porous body 5 can be used as a water-absorbing material.

[0141] In the manufacturing method of the present invention, a monomer aqueous solution with a neutralization rate of less than 70 mol% is used as a raw material. Here, the neutralization rate of the monomer aqueous solution is the ratio (in mol%) of the number of moles of neutralized monomers to the total number of moles of monomers (excluding internal crosslinking agents) in the monomer aqueous solution containing the monomer composition, and is the neutralization rate of the crosslinked polymer obtained from the monomer aqueous solution. Therefore, the absorbent material manufactured by the manufacturing method of the present invention is controlled to be weakly acidic; for example, compared with conventional absorbent materials, it can reduce skin roughness in users.

[0142] It should be noted that the manufacturing method of the present invention differs from the manufacturing method described in Patent Document 1, and can manufacture a water-absorbing material containing organic porous bodies without hydrolysis. Therefore, the manufacturing method of the present invention does not require the use of excess alkali necessary for hydrolysis. Thus, according to the manufacturing method of the present invention, a water-absorbing material containing organic porous bodies can be manufactured while arbitrarily adjusting the neutralization rate to a small value such as less than 70 mol%, resulting in, as previously mentioned, reducing skin roughness and other issues for users of this water-absorbing material.

[0143] Furthermore, the continuous pores of the organic porous body 5 are formed at the locations of the first solvent dispersed in the O / W emulsion 4. In the manufacturing method of the present invention, the O / W volume ratio in the O / W emulsion 4 is 2.5 or more. Therefore, the proportion of continuous pores in the organic porous body 5 is increased. In other words, in the organic porous body 5, the continuous framework occupies a small portion of the overall absorbent material, and the continuous pores occupy a large portion.

[0144] Here, as shown in the section on [2. Absorbent Material], when the portion occupied by the continuous pores is large, it becomes easier to draw the liquid into its interior, and it is easier to release the liquid when centrifugal force (pressure) is applied. Therefore, both the water absorption rate and the water release rate of the absorbent material containing the organic porous body 5 are improved.

[0145] As described above, the manufacturing method of the present invention can produce an absorbent material that, compared with conventional absorbent materials, reduces skin roughness for users and has excellent water absorption speed and water release rate.

[0146] Furthermore, in the manufacturing method of the present invention, an O / W emulsion with an O / W volume ratio adjusted to 2.5 or higher can be prepared by using a monomer aqueous solution with a neutralization rate of less than 70 mol% as a raw material. Then, the monomers contained in the monomer aqueous solution are polymerized in an O / W / O emulsion formed by dispersing the O / W emulsion in a second solvent, thereby producing a water-absorbing material comprising organic porous bodies. Additionally, in the manufacturing method of the present invention, the particle size is controlled during the O / W / O emulsion stage to produce a water-absorbing material comprising organic porous bodies. Therefore, the manufacturing method of the present invention can produce a water-absorbing material with a specified particle size without pulverizing the obtained organic porous bodies. It is known that pulverizing organic porous bodies results in the production of a large amount of fine powder, reducing productivity. Therefore, according to the manufacturing method of the present invention, a water-absorbing material with a specified particle size can be produced while avoiding the reduction in productivity caused by the production of a large amount of fine powder.

[0147] The following describes in detail each step of the manufacturing method constituting the present invention.

[0148] [3-1. O / W emulsion preparation process]

[0149] The O / W emulsion preparation step of the manufacturing method of the present invention is as follows: in a monomer aqueous solution with a neutralization rate of less than 70 mol%, in the presence of a first surfactant, a first solvent is encapsulated therein in such a way that the volume ratio of the first solvent to the monomer aqueous solution is 2.5 or more, thereby obtaining an O / W emulsion.

[0150] <Monomer aqueous solution>

[0151] The monomer aqueous solution is an aqueous solution containing monomers, which are the raw materials for the absorbent material to be manufactured, and any internal crosslinking agent, etc. The concentration of the monomer in the monomer aqueous solution is preferably 30% by mass to a saturation concentration relative to the total mass of the monomer aqueous solution, more preferably 35% to 45% by mass. The water used in the monomer aqueous solution is not particularly limited; examples include tap water, distilled water, and ion-exchanged water.

[0152] Furthermore, the manufacturing method of the present invention may include a monomer aqueous solution preparation step prior to the O / W emulsion preparation step, which involves preparing the monomer aqueous solution by dissolving the monomer and optionally an internal crosslinking agent in water. This step may include a step of adjusting the neutralization rate of the monomer aqueous solution. Known methods may be used to adjust the neutralization rate. Examples of such methods include, for instance, neutralizing the acid groups of the main component of the monomer in the manufacturing method of the present invention, namely (meth)acrylic acid (salt), using a compound containing an alkali metal. Examples of alkali metals include lithium, sodium, and potassium. Among these alkali metals, sodium and potassium are preferred. More than one alkali metal may be used.

[0153] The neutralization of the acid group can be achieved, for example, by adding an aqueous solution of an alkali metal-containing compound such as sodium hydroxide and / or potassium hydroxide dropwise to the monomer or an aqueous solution containing the monomer and mixing them. The concentration of the alkali metal-containing compound in the aqueous solution is not particularly limited, but is typically around 20–50% by mass.

[0154] (Monomer, internal cross-linking agent)

[0155] Regarding the monomer and internal crosslinking agent in the monomer aqueous solution, refer to the <monomer> and <internal crosslinking agent> columns of [2-1. crosslinking polymer] in [2. water-absorbing material]. It should be noted that the "neutralization rate of crosslinking polymer" recorded in the <monomer> column is equivalent to the "neutralization rate of monomer aqueous solution", and "content" is equivalent to the "amount used" in the manufacturing method of the present invention.

[0156] As a preferred example of the monomer aqueous solution, an aqueous solution containing an internal crosslinking agent, wherein the internal crosslinking agent is at least one selected from multifunctional acrylate crosslinking agents, acrylamide crosslinking agents, and glycidyl ether crosslinking agents, can be cited.

[0157] (Polymerization initiator)

[0158] When a polymerization initiator is used in the manufacturing method of the present invention, the polymerization initiator can be added to one or more of the monomer aqueous solution, O / W emulsion, and O / W / O emulsion at any time before the polymerization step is carried out. For uniform dispersion, the polymerization initiator is preferably added to the monomer aqueous solution in advance.

[0159] Water-soluble free radical polymerization initiators can be used as the polymerization initiator. Examples include persulfates such as potassium persulfate, sodium persulfate, and ammonium persulfate; azo-based polymerization initiators such as 2,2'-azobis(2-amidinylpropane) dihydrochloride and 2,2'-azobis(2-(2-imidazolin-2-yl)propane) dihydrochloride; hydrogen peroxide; and so on. The polymerization initiators that can be used in the manufacturing method of the present invention are not limited to those illustrated. Azo-based initiators and / or persulfates are preferred as the polymerization initiator. More than one polymerization initiator can be used.

[0160] The amount of polymerization initiator is usually preferably 0.05 to 10 millimoles relative to 1 mole of all monomers contained in the monomer aqueous solution.

[0161] <First Surfactant>

[0162] The first surfactant used in the O / W emulsion preparation process is not particularly limited as long as it can prepare the O / W emulsion. Examples of the first surfactant include: nonionic surfactants such as polyoxyethylene-polyoxypropylene copolymer, polyoxyethylene alkyl ether, polyoxypropylene alkyl ether, hydrophobically modified polyether urethane and hydrophobically modified polyester urethane, polyoxyethylene glycerol monostearate, polyoxyethylene glycerol monoisostearate, rosin ester and polyoxyethylene rosin ester; anionic surfactants such as sodium lauryl sulfate and polyoxyethylene sodium lauryl sulfate; and so on. The first surfactant is preferably a polyoxyethylene-polyoxypropylene copolymer from the compound. More than one first surfactant may be used.

[0163] Using a polyoxyethylene-polyoxypropylene copolymer as the first surfactant has the advantages of improving polymerization stability and forming a large number of continuous pores in the subsequent polymerization process, and is therefore preferred. For example, a polyoxyethylene-polyoxypropylene-polyoxyethylene block copolymer can be used as the polyoxyethylene-polyoxypropylene-polyoxyethylene copolymer.

[0164] From the viewpoint of improving the stability of polymerization during the polymerization process described later and forming a large number of continuous pores, the mass-average molecular weight of the polyoxyethylene-polyoxypropylene-polyoxyethylene block copolymer is preferably 3,000 or more, more preferably 5,000 or more. Furthermore, from the viewpoint of improving water solubility and workability, the mass-average molecular weight is preferably 100,000 or less, more preferably 30,000 or less. From these viewpoints, the mass-average molecular weight is preferably 3,000 to 100,000, more preferably 5,000 to 30,000.

[0165] The polyethylene oxide content in the polyoxyethylene-polyoxypropylene-polyoxyethylene block copolymer is preferably 40% by mass or more, more preferably 45% by mass or more. In this case, during the polymerization process described later, when the monomer is polymerized in the O / W / O emulsion, a good emulsification state of the O / W / O emulsion can be maintained, making it easy to form continuous pores inside the particles.

[0166] Furthermore, from the viewpoint of stabilizing the O / W emulsion dispersed in the O / W / O emulsion during the polymerization process described later, the content is preferably 90% by mass or less, more preferably 85% by mass or less. From these viewpoints, the content is preferably 40 to 90% by mass, more preferably 45 to 85% by mass.

[0167] Polyoxyethylene-polyoxypropylene-polyoxyethylene block copolymers are readily available industrially. Representative examples include the "Adeka Pluronic" (registered trademark) series manufactured by Asahi Denka Kogyo Co., Ltd., the "PLURONIC" (registered trademark) series manufactured by BASF, and the "Newpol" (registered trademark) series manufactured by Sanyo Chemical Co., Ltd. It should be noted that these polyoxyethylene-polyoxypropylene-polyoxyethylene block copolymers can be used individually or in combination of two or more types.

[0168] From the viewpoint of easily dispersing the first solvent in the monomer aqueous solution, the amount of the first surfactant relative to 100 parts by mass of the monomer aqueous solution is preferably 0.1 parts by mass or more, more preferably 0.5 parts by mass or more. Furthermore, even if the first surfactant is added in excess, the desired effect cannot be obtained, and it tends to become uneconomical. Therefore, the amount of the first surfactant relative to 100 parts by mass of the monomer aqueous solution is preferably 15 parts by mass or less, more preferably 10 parts by mass or less. From these viewpoints, the amount of the first surfactant relative to 100 parts by mass of the monomer aqueous solution is preferably 0.1 to 15 parts by mass, more preferably 0.5 to 10 parts by mass. There are no particular limitations on the object or timing of addition of the first surfactant, as long as it is used in the preparation of the O / W emulsion.

[0169] <First Solvent>

[0170] The first solvent used in the O / W emulsion preparation process is not particularly limited as long as it is a hydrophobic organic solvent and can be dispersed in the monomer aqueous solution to obtain the O / W emulsion. "The first solvent is dispersed in the monomer aqueous solution" means that the first solvent is encapsulated in the monomer aqueous solution.

[0171] The first solvent is preferably a hydrocarbon-based organic solvent selected from the group consisting of n-pentane, n-hexane, n-heptane, n-octane, cyclohexane, and methylcyclohexane. Among these, a solvent selected from the group consisting of n-hexane, n-heptane, and cyclohexane is more preferred because it is readily available industrially, has stable quality, and is relatively inexpensive.

[0172] Properties of monomeric aqueous solutions and O / W emulsions

[0173] In the manufacturing method of the present invention, the O / W volume ratio in the O / W emulsion preparation step is 2.5 or higher. The O / W volume ratio is the volume (mL) of the first solvent in the O / W emulsion / the volume (mL) of the monomer aqueous solution.

[0174] As mentioned above, by having an O / W volume ratio of 2.5 or higher, both the water absorption rate and the water separation rate of the absorbent material manufactured by the method of the present invention can be improved. It should be noted that the O / W volume ratio can be controlled, for example, by adjusting the amount of the first solvent used in the O / W emulsion preparation step.

[0175] From the viewpoint of improving both the water absorption rate and the water separation rate of the absorbent material, the O / W volume ratio is preferably 2.5 or more, more preferably 2.8 or more, even more preferably 3.0 or more, even more preferably 3.2 or more, and even more preferably 5.0 or more. Furthermore, when the O / W volume ratio is below a specific value, emulsification is stabilized, the monomer aqueous solution can adequately encapsulate the first solvent, and the O / W emulsion can be prepared well. From this viewpoint, the O / W volume ratio is preferably 15.0 or less, more preferably 10.0 or less.

[0176] From the viewpoint of improving the porosity of the obtained particles by stabilizing the O / W emulsion, the viscosity of the monomer aqueous solution at 25°C is preferably 500 MPa·s or more, and more preferably 1000 MPa·s or more.

[0177] The viscosity of the monomer aqueous solution can be adjusted, for example, using a polymeric thickener.

[0178] As the polymeric thickener, hydroxyethyl cellulose, carboxymethyl cellulose, guar gum, gum arabic, glucomannan, dextrin, polyvinyl alcohol, polyethylene oxide, and partially neutralized polyacrylic acid are preferred, for example. This is because these polymeric thickeners, even in small amounts, can impart a high viscosity to the monomer aqueous solution. More than one polymeric thickener may be used.

[0179] <Conditions of the O / W emulsion preparation process, etc.>

[0180] The method for preparing the O / W emulsion in the O / W emulsion preparation process is not particularly limited. For example, one method may involve mixing a first surfactant in an aqueous monomer solution, stirring the resulting mixture, and then slowly adding a first solvent to it.

[0181] From the viewpoint of the stability of the O / W emulsion, the liquid temperature of the monomer aqueous solution when preparing the O / W emulsion is preferably below 30°C, and more preferably 15 to 25°C.

[0182] It should be noted that a stirring device or the like can be used when preparing the O / W emulsion. The stirring device is not particularly limited; for example, it can be a homogenizer or other device capable of fine emulsification, or it can be a general stirring blade such as a paddle, propeller, or screw. Any stirring device can appropriately adjust the number and size of pores in the resulting particles by adjusting the stirring speed, etc.

[0183] [3-2. O / W / O emulsion preparation process]

[0184] The O / W / O emulsion preparation step of the manufacturing method of the present invention is a step of dispersing the O / W emulsion prepared in the O / W emulsion preparation step in a second solvent to obtain an O / W / O emulsion. It should be noted that, from the viewpoint of obtaining a good O / W / O emulsion, it is preferable that the second solvent contains a second surfactant.

[0185] <Second solvent>

[0186] The second solvent used in the O / W / O emulsion preparation process is the dispersion medium for the O / W emulsion. There are no particular limitations as long as the second solvent is a hydrophobic organic solvent capable of dispersing the O / W emulsion to obtain an O / W / O emulsion. For example, a hydrocarbon-based organic solvent selected from the group consisting of n-pentane, n-hexane, n-heptane, n-octane, cyclohexane, and methylcyclohexane is preferred as the second solvent. Among these, solvents selected from the group consisting of n-hexane, n-heptane, and cyclohexane are more preferred because they are readily available industrially, have stable quality, and are relatively inexpensive.

[0187] It should be noted that the first solvent and the second solvent can be of the same type or different types. From the viewpoint of facilitating the reuse of solvents recovered in the drying process described later, it is preferable that the first solvent and the second solvent are of the same type.

[0188] <Second Surfactant>

[0189] Examples of the second surfactant include sucrose fatty acid esters, (poly)glycerol fatty acid esters, sorbitan fatty acid esters, polyoxyethylene sorbitan fatty acid esters, polyoxyethylene glycerol fatty acid esters, sorbitol fatty acid esters, polyoxyethylene sorbitol fatty acid esters, polyoxyethylene alkyl ethers, polyoxyethylene alkylphenyl ethers, polyoxyethylene castor oil, polyoxyethylene hydrogenated castor oil, alkylallyl formaldehyde condensed polyoxyethylene ethers, polyoxyethylene polyoxypropylene block copolymers, polyoxyethylene polyoxypropyl alkyl ethers, polyethylene glycol fatty acid esters, alkyl glucosides, N-alkyl glucose amides, polyoxyethylene fatty acid amides, polyoxyethylene alkyl amines, phosphate esters of polyoxyethylene alkyl ethers, phosphate esters of polyoxyethylene alkyl allyl ethers, and the like. These may be used alone respectively, or two or more of them may be used in combination.

[0190] The second surfactant is preferably at least one selected from the group consisting of sucrose fatty acid esters, sorbitan fatty acid esters, sorbitol fatty acid esters and polyglycerol fatty acid esters, and sucrose fatty acid esters are more preferred due to their excellent safety.

[0191] It should be noted that in the present specification, "(poly)" covers both the case with the prefix "poly" and the case without the prefix "poly".

[0192] From the viewpoint of ensuring stability during polymerization in the polymerization step described later, the amount of the second surfactant is preferably 0.5 parts by mass or more, more preferably 1 part by mass or more, relative to 100 parts by mass of the aqueous monomer solution. In addition, the amount of the second surfactant is preferably 10 parts by mass or less, more preferably 5 parts by mass or less, relative to 100 parts by mass of the aqueous monomer solution. This is because even if the second surfactant is added in excess, the corresponding effect cannot be obtained, and instead it tends to become uneconomical. From these viewpoints, the amount of the second surfactant is preferably 0.5 to 10 parts by mass, more preferably 1 to 5 parts by mass, relative to 100 parts by mass of the aqueous monomer solution.

[0193] <Conditions for the O / W / O emulsion preparation step>

[0194] The method for preparing the O / W / O emulsion in the O / W / O emulsion preparation step is not particularly limited. Examples of the method include the following method: delivering the O / W emulsion into the second solvent using a liquid delivery device such as a tube pump, and adding the O / W emulsion while stirring. There is no particular limitation on the device used for stirring, for example, paddle-type stirring blades used for stirring in a flask can be used.

[0195] [3-3. Polymerization Step]

[0196] The polymerization step of the manufacturing method of the present invention is to polymerize the monomer contained in the monomer aqueous solution in the O / W / O emulsion prepared in the O / W / O emulsion preparation step to prepare an organic porous body.

[0197] The reaction temperature during the polymerization of the monomer in the polymerization process varies depending on the type of polymerization initiator used, and therefore cannot be generalized. Regarding the reaction temperature, from the viewpoint of improving economy by accelerating the polymerization reaction and shortening the polymerization time, and from the viewpoint of conducting the polymerization reaction in a manner that prevents the first or second organic solvent from boiling, 40–100°C is preferred, and 50–80°C is more preferred.

[0198] It should be noted that, when the reaction temperature is above 60°C, from the viewpoint of maintaining the stability of the O / W / O emulsion during the polymerization reaction of the monomers, a polymeric dispersion stabilizer is preferred. Suitable polymeric dispersion stabilizers include: maleic anhydride-modified polyethylene, maleic anhydride-modified polypropylene, maleic anhydride-modified ethylene-propylene copolymer, maleic anhydride-modified ethylene-propylene-diene terpolymer (EPDM), maleic anhydride-modified polybutadiene, maleic anhydride-ethylene copolymer, maleic anhydride-propylene copolymer, maleic anhydride-ethylene-propylene copolymer, maleic anhydride-butadiene copolymer, polyethylene, polypropylene, ethylene-propylene copolymer, oxidized polyethylene, oxidized polypropylene, oxidized ethylene-propylene copolymer, ethylene-acrylic acid copolymer, ethyl cellulose, and hydroxyethyl cellulose, etc.

[0199] From the perspective of the dispersion stability of monomeric aqueous solutions, suitable polymeric dispersion stabilizers include: maleic anhydride-modified polyethylene, maleic anhydride-modified polypropylene, maleic anhydride-modified ethylene-propylene copolymer, maleic anhydride-ethylene copolymer, maleic anhydride-propylene copolymer, maleic anhydride-ethylene-propylene copolymer, polyethylene, polypropylene, ethylene-propylene copolymer, oxidized polyethylene, oxidized polypropylene, and oxidized ethylene-propylene copolymer. The polymeric dispersion stabilizer can be one type or a mixture of two or more polymeric dispersion stabilizers. Furthermore, these polymeric dispersion stabilizers and the second surfactant can be used together.

[0200] From the viewpoint of sufficiently stabilizing the O / W / O emulsion, the amount of the polymeric dispersion stabilizer relative to 100 parts by mass of the monomer aqueous solution is preferably 0.5 parts by mass or more, more preferably 1 part by mass or more. Furthermore, the amount of the polymeric dispersion stabilizer relative to 100 parts by mass of the monomer aqueous solution is preferably 10 parts by mass or less, more preferably 5 parts by mass or less. This is because, in cases where an excessive amount of the polymeric dispersion stabilizer is added, the desired effect may not be achieved, and it may become uneconomical.

[0201] It should be noted that the reaction time of the polymerization reaction is not particularly limited, but is usually about 0.5 to 3 hours.

[0202] [3-4. Post-crosslinking process]

[0203] Through the polymerization process, the organic porous body is typically obtained in the form of hydrogel particles. From the viewpoint of improving the water absorption rate and gel strength of the organic porous body and the absorbent material containing it, the manufacturing method of the present invention may include a post-crosslinking process in which the organic porous body obtained by the polymerization process undergoes a post-crosslinking reaction. In this post-crosslinking process, the crosslinked polymer constituting the organic porous body is post-crosslinked, i.e., surface-crosslinked. Through this post-crosslinking process, an organic porous body formed from the surface-crosslinked crosslinked polymer and the continuous pores can be obtained. Hereinafter, the organic porous body obtained by the post-crosslinking process will also be referred to as a "surface-crosslinked organic porous body".

[0204] <Post-crosslinking agent>

[0205] As the post-crosslinking agent, a crosslinking agent capable of reacting with the reactive groups in the crosslinked polymer can be used.

[0206] Specific examples of the post-crosslinking agent include: polyols such as ethylene glycol, propylene glycol, trimethylolpropane, glycerol, (poly)oxyethylene glycol, polyoxypropylene glycol, and polyglycerol; ether compounds having two or more glycidyl groups, such as (poly)ethylene glycol diglycidyl ether, (poly)propylene glycol diglycidyl ether, and (poly)glycerol triglycidyl ether; and compounds having two or more reactive functional groups, such as halogenated epoxy compounds, such as epichlorohydrin, epibromopropane, and α-methylepoxychloropropane. These can be used alone or in combination. Among the post-crosslinking agents, (poly)ethylene glycol diglycidyl ether is preferred.

[0207] The amount of the post-crosslinking agent varies depending on the moisture content of the crosslinking polymer and the processing temperature, and therefore cannot be generalized. It should be noted that the moisture content of the crosslinking polymer is the same as the moisture content of the organic porous body.

[0208] The post-crosslinking agent can be added at any time after the polymerization reaction is complete. Regarding the timing of this addition, from the viewpoint of fully initiating the post-crosslinking reaction and increasing the water absorption rate of the absorbent material, it is preferable when the water content of the crosslinked polymer is 10% by mass or more, and more preferably 20% by mass or more. Furthermore, from the viewpoint of preventing the water retention capacity of the absorbent material from becoming too low, it is preferable when the water content of the crosslinked polymer is 80% by mass or less, and more preferably 65% ​​by mass or less. From these viewpoints, the preferred timing for adding the post-crosslinking agent is when the water content of the crosslinked polymer is 10–80% by mass, and more preferably 20–65% by mass.

[0209] <Dehydration Treatment>

[0210] The post-crosslinking process may include a dehydration treatment to adjust the moisture content of the crosslinked polymer by removing water from the polymer before adding the post-crosslinking agent. Known methods may be used as dehydration methods. Examples of such methods include, for instance, the removal of water and hydrophobic organic solvents by distillation using an azeotropic distillation column.

[0211] It should be noted that the water content and solid content of the hydrogel, i.e. the solid content of the crosslinked polymer, can be calculated based on the amount of monomers and other raw material compounds added in the polymerization reaction and the amount of water removed in the dehydration and drying processes described later.

[0212] <Methods and conditions for post-crosslinking>

[0213] The post-crosslinking reaction in the post-crosslinking process can be carried out, for example, by adding a solution of a post-crosslinking agent to an aqueous gel obtained by subjecting the hydrogel after the polymerization reaction to the dehydration treatment and adjusting it to a specified water content.

[0214] The post-crosslinking agent solution refers to, for example, a solution prepared by dissolving the post-crosslinking agent in water or alcohol, with a concentration of 0.5% to 50% by mass. During the post-crosslinking reaction, the solution of the post-crosslinking agent can be dried immediately after addition, and more preferably, the internal temperature can be maintained at 50 to 90°C for 0.5 to 6 hours to promote the post-crosslinking reaction. The internal temperature refers to the temperature of the hydrogel after the addition of the solution of the post-crosslinking agent, i.e., the mixture of the solution of the post-crosslinking agent and the hydrogel.

[0215] [3-5. Drying process]

[0216] The manufacturing method of the present invention may include a drying process of removing water and hydrophobic organic solvents from the organic porous body obtained by the polymerization process or the surface-crosslinked organic porous body obtained by the post-crosslinking process.

[0217] As a method for removing the water and hydrophobic organic solvent, known methods can be employed. Examples of such methods include: distilling the water and hydrophobic organic solvent using an azeotropic distillation column, filtration, and vacuum drying. This method can employ only one method or a combination of two or more methods. By implementing the drying process, a water-absorbing material with low moisture content and in a dry state can be readily produced.

[0218] [3-6. Chelating agent mixing process]

[0219] The manufacturing method of the present invention may include a chelating agent mixing step of mixing the monomer aqueous solution or the organic porous body with a chelating agent. The organic porous body may be an organic porous body obtained in the polymerization step, or a surface-crosslinked organic porous body obtained after the post-crosslinking step.

[0220] The type and amount of chelating agent used in the chelating agent mixing process are not particularly limited. The description of the type and content of chelating agent in the [2-4. Chelating Agent] section of [2. Absorbent Material] can be referenced.

[0221] [3-7. Inorganic Particle Mixing Process]

[0222] The manufacturing method of the present invention may include an inorganic particle mixing step of mixing the organic porous body with inorganic particles. The organic porous body may be an organic porous body obtained in the polymerization step, or a surface-crosslinked organic porous body obtained after the post-crosslinking step.

[0223] The types and amounts of inorganic particles used in the inorganic particle addition process are not particularly limited. The description of the types and contents of inorganic particles in the [2-5. Inorganic Particles] section of [2. Absorbent Material] can be referenced.

[0224] [3-8. Mixing process for other additives]

[0225] The manufacturing method of the present invention may include a step of mixing the organic porous body with other additives. The organic porous body may be an organic porous body obtained in the polymerization step, or a surface-crosslinked organic porous body obtained after the post-crosslinking step.

[0226] There are no particular limitations on the types and amounts of other additives used in this process. The information on the types and amounts of other additives can be found in the section on [2. Absorbent Materials] [2-6. Other Additives].

[0227] [3-9. Recycling Process]

[0228] The manufacturing method of the present invention may include a recovery step of separating and recovering microparticles from the manufactured organic porous body. The separated microparticles can be added to various steps such as the O / W emulsion preparation step and the O / W / O emulsion preparation step for reuse.

[0229] One embodiment of the present invention may include the inventions shown below [1] to

[13] .

[0230] [1] An absorbent material comprising an organic porous body having a continuous framework formed of a cross-linked polymer whose main components are structural units derived from (meth)acrylate (salt), and continuous pores.

[0231] The centrifugal retention capacity (CRC) of the absorbent material is 5–25 g / g.

[0232] The bulk density is less than 0.3 g / ml, and,

[0233] The neutralization rate of the crosslinked polymer is less than 70 mol%.

[0234] [2] According to the absorbent material described in [1], the absorption rate (Vortex) of the physiological saline of the absorbent material is less than 10 seconds.

[0235] [3] The absorbent material according to [1] or [2], wherein the free swelling ratio (FSC) of the absorbent material is 35 g / g or more.

[0236] [4] The absorbent material according to any one of [1] to [3], wherein the water separation rate of the absorbent material, expressed by the following formula (1), is 40% or more:

[0237] Water separation rate [%] = {(FSC[g / g] - CRC[g / g]) / FSC[g / g]} × 100··(1)

[0238] [5] The absorbent material according to any one of [1] to [4], wherein the absorbent material contains a chelating agent.

[0239] [6] The absorbent material according to any one of [1] to [5], wherein the absorbent material comprises inorganic microparticles.

[0240] [7] A method for manufacturing a water-absorbing material, the water-absorbing material comprising an organic porous body having a continuous framework formed by a cross-linked polymer with structural units derived from (meth)acrylate (salt) as the main component, and continuous pores, the manufacturing method comprising:

[0241] In the O / W emulsion preparation process, in a monomer aqueous solution with a neutralization rate of less than 70 mol%, a first solvent is encapsulated therein in the presence of a first surfactant, such that the volume ratio of the first solvent to the monomer aqueous solution is 2.5 or more, thereby obtaining an O / W emulsion.

[0242] The O / W / O emulsion preparation process involves dispersing the O / W emulsion in a second solvent to obtain an O / W / O emulsion; and

[0243] In the polymerization process, monomers contained in the monomer aqueous solution are polymerized in the O / W / O emulsion to prepare an organic porous body.

[0244] [8] According to the method for manufacturing the absorbent material described in [7], wherein the monomer aqueous solution contains a polymerization initiator.

[0245] The polymerization initiator is an azo initiator and / or persulfate.

[0246] [9] The method for manufacturing the absorbent material according to [7] or [8], wherein the monomer aqueous solution contains an internal crosslinking agent.

[0247] The internal crosslinking agent is selected from at least one of the group consisting of multifunctional acrylate crosslinking agents, acrylamide crosslinking agents, and glycidyl ether crosslinking agents.

[0248]

[10] The method for manufacturing the absorbent material according to any one of [7] to [9], wherein the first surfactant is a polyoxyethylene-polyoxypropylene-polyoxyethylene block copolymer.

[0249]

[11] The method for manufacturing the absorbent material according to any one of [7] to

[10] , wherein the second solvent contains a second surfactant.

[0250]

[12] According to the method for manufacturing the absorbent material described in

[11] , wherein the second surfactant is at least one selected from the group consisting of sucrose fatty acid ester, dehydrated sorbitol fatty acid ester, sorbitol fatty acid ester and polyglycerol fatty acid ester.

[0251]

[13] The method for manufacturing the absorbent material according to any one of [7] to

[12] , wherein the first solvent and the second solvent are of the same type.

[0252]

[14] A composite absorbent comprising the absorbent material described in any one of [1] to [6] and absorbent resin particles.

[0253] This invention is not limited to the embodiments described above. Various modifications can be made within the scope of the claims. Embodiments obtained by appropriately combining the technical means disclosed in different embodiments are also included within the technical scope of this invention.

[0254] Example

[0255] [Determination and Calculation of Physical Properties]

[0256] The physical properties of the absorbent materials 1 to 6 and the comparative absorbent material 1 manufactured in Examples 1 to 6 and Comparative Example 2 were measured and calculated using the following methods.

[0257] Centrifuge Retention Capacity (CRC)

[0258] The CRC of the absorbent material was determined according to NWSP 241.0.R2 (15). Specifically, 0.2 g of absorbent material was placed in a nonwoven bag and then immersed in a large amount of excess 0.9% sodium chloride aqueous solution for 30 minutes to allow the absorbent material to swell freely. Then, it was dehydrated by centrifuging (250G) for 3 minutes, and then the CRC (unit: g / g) was determined.

[0259] Bulk density

[0260] Add absorbent material to a 10 mL (2.5 cm inner diameter) cylindrical plastic container until it bulges and spills outside the container. Then, use a flat scraper to level the absorbent material on the surface of the container. At this point, to prevent the absorbent material from densely filling the container, the operation should be performed with minimal vibration. Then, calculate the weight of the absorbent material in the container based on the weight change (difference) of the container before and after filling. Divide this weight by the container volume (10 mL) to determine the bulk density of the absorbent material (unit: g / mL).

[0261] <Water absorption rate (Vortex)>

[0262] Add 0.02 parts by weight of Food Blue No. 1 as a food additive to 1000 parts by weight of 0.90% sodium chloride aqueous solution (physiological saline), and adjust the liquid temperature to 30°C. Measure 50 ml of this physiological saline into a 100 ml beaker, and stir at 600 rpm using a cylindrical stir bar with a length of 40 mm and a diameter (diameter of the cross section perpendicular to the length direction of the cylinder). During this process, add 2.0 g of absorbent material, and measure the Vortex (absorption rate in seconds) of the absorbent material.

[0263] Regarding the endpoint of the water absorption rate determination, according to the standard described in JIS K 7224-1996 "Explanation of the test method for water absorption rate of superabsorbent resin", the time (Vortex: seconds) until the sample absorbs physiological saline and the test liquid covers the tip of the stir bar is used as the water absorption rate (seconds).

[0264] Free Swelling Ratio (FSC)

[0265] The FSC of the absorbent material was determined according to NWSP 240.0.R2 (15). Specifically, 0.2 g of absorbent material was placed in a nonwoven bag and then immersed in a large amount of excess 0.90% sodium chloride aqueous solution for 30 minutes to allow it to swell freely. Then, the bag was lifted and suspended for 10 minutes to drain the water, and the absorbency ratio after water draining was calculated (unit: g / g).

[0266] <Water Diversion Rate>

[0267] Using the CRC and FSC of the absorbent material, the water separation rate of the absorbent material is calculated based on the following formula (1).

[0268] Water separation rate [%] = {(FSC[g / g] - CRC[g / g]) / FSC[g / g]} × 100 · · (1)

[0269] <ph>

[0270] The pH of the absorbent material was determined according to NWSP 200.0.R2 (15). Specifically, 100 ml of a 0.90% by mass sodium chloride aqueous solution at 23°C was measured into a beaker. Then, while stirring the sodium chloride aqueous solution in the beaker at 150 rpm with a cylindrical stirrer with a length of 40 mm and a diameter (diameter of the cross section perpendicular to the length direction of the cylinder), 0.5 g of absorbent material was added to the sodium chloride aqueous solution. Then, the sodium chloride aqueous solution was stirred for 10 minutes to allow the absorbent material to swell. Then, a pH electrode was inserted into the sodium chloride aqueous solution, and the pH value was read at the point of stabilization.

[0271] <Mass average particle size (D50)>

[0272] The mass-average particle size (D50) of the absorbent material was determined according to "(3) Mass-Average Particle Diameter (D50) and Logarithmic Standard Deviation (σζ) of Particle Diameter Distribution" as described in columns 27 and 28 of U.S. Patent No. 7638570.

[0273] <Increase in Micronized Powder Content (Damage Test)>

[0274] The increase in the amount of micronized powder in the absorbent material was determined as described below.

[0275] Add 10g of 6mm diameter soda-lime glass beads (precision fractionation filling soda-lime glass beads) and 3g of absorbent to a 242ml glass container (225ml with inner lid) (a mayonnaise jar manufactured by Yamamura Glass Co., Ltd., 6cm in diameter and 11cm in height). After sealing the container with a resin inner lid (made of polyethylene) and an outer lid (made of polypropylene), use a Paint Shaker (Toyo Seiki Seisakusho No. 488) to agitate at 800 cycles / min (CPM) for 10 minutes, thereby inflicting mechanical damage on the absorbent material.

[0276] Next, the samples before and after the damage test were sieved using a JIS standard sieve with a mesh size of 150 μm. The ratio of the micro powder passing through the sieve to the test sample was taken as the amount of micro powder (weight %), and the increase in amount before and after the test was calculated (amount of micro powder after the test - amount of micro powder before the test).

[0277] [Example 1]

[0278] (1) Preparation of O / W emulsion

[0279] Prepare a 1000mL four-necked detachable flask (1) (hereinafter referred to as "flask (1)") equipped with a stirrer, a dropping funnel, a fluoropolymer tubing for nitrogen blowing, and a thermometer. Add 16.85g of acrylic acid, 39.63g of a 37% by mass sodium acrylate aqueous solution, and 2.00g of methylenebisacrylamide to the flask (1). The neutralization rate of the acrylic acid (salt) is 40 mol%. Next, add 0.64g of hydroxyethyl cellulose to the flask (1) and stir.

[0280] In addition, 2.27 g of a polyoxyethylene-polyoxypropylene copolymer (manufactured by Asahi Denka Kogyo Co., Ltd., trade name: AdekaPluronic F-108, mass average molecular weight: 15500) was dissolved in 21.61 g of deionized water to prepare aqueous solution A. Furthermore, 0.05 g of 2,2'-azobis(2-methylpropanediamine) dihydrochloride was dissolved in 2.59 g of deionized water to prepare aqueous solution B.

[0281] Aqueous solutions A and B were added to the flask (1) to mix and dissolve them, thus preparing a monomer aqueous solution. Then, while stirring the monomer aqueous solution at 600 rpm, 433.3 g (646 mL) of n-heptane was added dropwise to the monomer aqueous solution at a flow rate of 11 mL / min. As a result, an O / W emulsion of n-heptane dispersed in the monomer aqueous solution was obtained. The O / W volume ratio of the O / W emulsion was 88 / 12 = 7.3.

[0282] (2) Preparation of O / W / O emulsion

[0283] Prepare a 2000 mL four-necked detachable flask (2) (hereinafter referred to as "flask (2)") equipped with a stirrer, reflux cooling tube, nitrogen blowing tubing made of fluoropolymer resin and a thermometer, and inject 670 g (1000 mL) of n-heptane into the flask (2). Next, add 3.11 g of sucrose fatty acid ester [manufactured by Mitsubishi Chemical Foods Co., Ltd., trade name: S-370] and 3.11 g of maleic anhydride modified polyethylene [Mitsui Chemicals Co., Ltd., trade name: HI-WAX1105A] to the flask (2).

[0284] Next, while stirring with nitrogen gas being blown into the flask (2) at a flow rate of 100 mL / min, the flask (2) was immersed in a hot water bath at 80°C and stirred until the contents of the flask became homogeneous. Then, the speed of the stirrer was set to 700 rpm, and the contents of the flask (2) were naturally cooled to 60°C while stirring. Then, the O / W emulsion prepared in (1) was added dropwise to the flask (2) at a flow rate of 60 mL / min to prepare an O / W / O emulsion.

[0285] (3) Polymerization and drying

[0286] The flask (2) containing the O / W / O emulsion prepared in (2) was immersed in a hot water bath at 70°C to raise the temperature of the O / W / O emulsion. The stirring speed was set to 700 rpm, and the polymerization reaction was carried out for 1.5 hours while stirring. Then, the O / W / O emulsion after the polymerization reaction was subjected to azeotropic distillation at 100°C to dehydrate it and obtain a slurry.

[0287] The solvent was removed from the slurry by filtration through a sieve with a mesh size of 125 μm, yielding a filter media. This filter media was then dried under reduced pressure at 60°C for 2 hours to produce 35 g of an organic porous body with a mass-average particle size of 554 μm. This organic porous body was used as absorbent material 1.

[0288] [Example 2]

[0289] Except for the changes shown in (i) and (ii) below, the organic porous body was manufactured using the same method as in Example 1. It should be noted that the neutralization rate of the acrylic acid (salt) used in Example 2 was 50 mol%.

[0290] (i) Change the amount of acrylic acid to 13.67g.

[0291] (ii) The amount of 37% sodium acrylate aqueous solution was changed to 48.23 g.

[0292] The fabricated organic porous body has a mass-average particle size of 524 μm and a mass of 34 g. This organic porous body is designated as absorbent material 2.

[0293] [Example 3]

[0294] Except for the changes shown in (iii) and (iv) below, the organic porous body was manufactured using the same method as in Example 2. It should be noted that the neutralization rate of the acrylic acid (salt) used in Example 3 was the same as in Example 2, at 50 mol%.

[0295] (iii) Replace 2.00g of methylene bisacrylamide with 6.59g of polyethylene glycol diacrylate (n-9).

[0296] (iv) The aqueous solution of 2,2'-azobis(2-methylpropanediamine) dihydrochloride was changed to an aqueous solution prepared by dissolving 0.05 g of sodium persulfate in 0.4 g of ion-exchanged water.

[0297] The fabricated organic porous body has a mass-average particle size of 542 μm and a mass of 34 g. This organic porous body is designated as absorbent material 3.

[0298] [Example 4]

[0299] Except for the changes shown in (v) and (vi) below, the organic porous body was manufactured using the same method as in Example 2. It should be noted that the neutralization rate of the acrylic acid (salt) used in Example 4 was the same as in Example 2, at 50 mol%. Furthermore, the O / W volume ratio of the O / W emulsion in Example 4 was 76 / 24 = 3.2.

[0300] (v) The amount of n-heptane used in the preparation of the O / W emulsion was changed to 216.7 g (323 mL).

[0301] (vi) Change the speed of the mixer during the preparation of O / W / O emulsion to 350 rpm.

[0302] The fabricated organic porous body has a mass-average particle size of 478 μm and a mass of 33 g. This organic porous body is designated as absorbent material 4.

[0303] [Example 5]

[0304] Except for the changes shown in (vii) and (viii) below, the organic porous body was manufactured by the same method as in Example 1. It should be noted that the neutralization rate of the acrylic acid (salt) used in Example 5 was 60 mol%.

[0305] (vii) Change the amount of acrylic acid to 10.66g.

[0306] (viii) The amount of 37% sodium acrylate aqueous solution was changed to 56.36 g.

[0307] The manufactured organic porous body has a mass-average particle size of 488 μm and a mass of 35 g. This organic porous body is designated as absorbent material 5.

[0308] [Example 6]

[0309] The organic porous body obtained in Example 2 was processed by performing the following steps (ix) and (x) to produce an organic porous body.

[0310] (ix) For 100 parts by weight of the organic porous body obtained in Example 2, 1.0 part by weight of pure water and 0.01 parts by weight of trisodium diethylenetriaminepentaacetate (DTPA·3Na) were uniformly mixed. Then, under windless conditions, the mixture was heated at 60°C for 45 minutes and then crushed until it passed through a JIS standard sieve with an 850 μm sieve opening.

[0311] (x) 1.0 part by weight of silica (product name Aerosil 200CF, manufactured by Nippon Aerosil Co., Ltd.) was mixed into 100 parts by weight of the organic porous body obtained through process (ix). The mixing was carried out by placing 6 g of the organic porous body together with the silica into a mayonnaise jar manufactured by Yamamura Glass Co., Ltd. used in the damage test, tightening the inner and outer caps, and then applying vibration with a Paint Shaker (manufactured by Toyo Seiki) (1 minute at room temperature).

[0312] The mass-average particle size of the manufactured organic porous body is 520 μm. This organic porous body is designated as water-absorbing material 6.

[0313] [Comparative Example 1]

[0314] Except for the changes shown in (xi) and (xii) below, the same method as in Example 1 was implemented. It should be noted that the neutralization rate of the acrylic acid (salt) used in Comparative Example 1 was 75 mol%.

[0315] (xi) The amount of acrylic acid was changed to 6.41g.

[0316] (xii) The amount of 37% sodium acrylate aqueous solution was changed to 67.85g.

[0317] As a result, the monomer aqueous solution and n-heptane did not emulsify during the preparation of the O / W emulsion, and phase separation occurred, thus failing to produce an organic porous body.

[0318] [Comparative Example 2]

[0319] Organic porous bodies are manufactured using the same method as in Example 1 of Patent Document 1, specifically the method shown below.

[0320] 9.2 g of tert-butyl methacrylate, 0.28 g of divinylbenzene, 1.0 g of sorbitan monooleate and 0.4 g of 2,2'-azobis(isobutyronitrile) were mixed and dissolved uniformly to obtain a mixture.

[0321] While stirring the mixture, 180g of pure water was added to it to obtain a water-in-oil emulsion. The O / W volume ratio of the water-in-oil emulsion was 8 / 92 = 0.087.

[0322] The resulting emulsion was quickly transferred to a reaction vessel, sealed, and allowed to stand at 60°C for 24 hours to allow the monomers in the emulsion to polymerize.

[0323] After polymerization, the contents of the reaction vessel were removed, coarsely pulverized into 1 cm cubes, and then extracted with methanol to obtain an extract. The extract was then dried under reduced pressure to obtain a dried product.

[0324] The obtained dried material was impregnated in dichloroethane containing zinc bromide. Then, after stirring at 40°C for 24 hours, it was sequentially contacted with methanol, 4% hydrochloric acid, 4% sodium hydroxide aqueous solution, and water to hydrolyze the dried material. The resulting hydrolysate was dried, pulverized, and classified to obtain an organic porous body with a mass-average particle size in the range of 500–850 μm. This organic porous body is designated as comparative absorbent material 1.

[0325] [in conclusion]

[0326] The manufacturing conditions of Examples 1-6 and Comparative Examples 1-2, as well as the physical property values ​​of absorbent materials 1-6 and comparative absorbent material 1 measured and calculated by the method described above, are shown in Tables 1 and 2 below.

[0327] [Table 1]

[0328]

[0329] [Table 2]

[0330]

[0331] ★ In Table 2, "-" indicates that the increase in micronized powder was not measured.

[0332] As shown in Table 1, in the manufacturing methods of the absorbent materials in Examples 1-6, the neutralization rate of the monomer aqueous solution is less than 70 mol%, and the O / W volume ratio of the O / W emulsion is 2.5 or higher, which meets the requirements of the manufacturing method of the present invention. Therefore, the manufacturing methods of the absorbent materials in Examples 1-6 belong to the manufacturing methods of the present invention.

[0333] Furthermore, it is obvious that since the neutralization rate of the monomer aqueous solutions in Examples 1-6 is less than 70 mol%, the neutralization rate of the crosslinked polymers in absorbent materials 1-6 is also less than 70 mol%. Moreover, as shown in Table 2, absorbent materials 1-6 have a CRC of 5-25 g / g and a bulk density of less than 0.3 g / ml. Therefore, absorbent materials 1-6 belong to the absorbent materials of the present invention.

[0334] Therefore, the water-absorbing material of the present invention can be manufactured using the manufacturing method of the present invention.

[0335] As shown in Table 2, the pH values ​​of absorbent materials 1 to 6 range from 4.7 to 5.6, indicating they are weakly acidic. Therefore, it can be seen that absorbent materials 1 to 6 can reduce skin roughness compared to previous absorbent materials. Furthermore, absorbent materials 1 to 6 have sufficiently low Vortex values ​​and sufficiently high water separation rates, thus demonstrating excellent absorption speed and water separation rate.

[0336] As can be seen from the above, the absorbent material of the present invention, compared with conventional absorbent materials, can reduce skin roughness and other issues for the user, and exhibits superior absorption speed and water release rate. Furthermore, it is known that the manufacturing method of the present invention can produce the aforementioned absorbent material.

[0337] It should be noted that in the conventional manufacturing method shown in Comparative Example 1, the absorbent material could not be manufactured when the O / W volume ratio was set to 2.5 or higher. On the other hand, a comparison between Examples 1 to 6 and Comparative Example 1 shows that the manufacturing method of the present invention can manufacture an absorbent material even when the O / W volume ratio is set to 2.5 or higher by adjusting the neutralization rate of the monomer aqueous solution to less than 70 mol%.

[0338] Industrial availability

[0339] This invention is preferably used for applications requiring reduced skin roughness compared to conventional absorbent materials, as well as high absorbency and high water release rate. Examples of such applications include: using it as a substitute for hydrophilic fibers such as pulp that have traditionally been used in sanitary materials such as diapers, sanitary napkins, absorbent shorts / pads, and nursing pads; or using it as an absorbent polymer for the aforementioned sanitary materials; and so on. In addition, examples of other uses include: soil moisture retention agents, seedling sheets, seed coating materials, anti-condensation sheets, leakage absorption materials, preservation materials, disposable heat packs, cooling headscarves, cold insulators, medical waste liquid solidifying agents, residual soil solidifying materials, waterproof waste liquid gelling agents, absorbent sandbags, disaster relief makeshift toilets, wet dressing materials, thickeners for cosmetics, waterproofing materials for electrical, electronic and communication cables, gasket sealing materials, slow-release agents for fertilizers, various slow-release agents (space sterilizers, fragrances, etc.), pet mats, cat litter, wound dressings, anti-condensation building materials, and oil moisture removal agents.

[0340] Symbol Explanation

[0341] 1: First solvent

[0342] 2: Monomer aqueous solution

[0343] 3: Second solvent

[0344] 4: O / W emulsion

[0345] 5: Organic porous bodies< / ph> < / ph>

Claims

1. An absorbent material comprising an organic porous body having a continuous framework formed of a cross-linked polymer whose main components are structural units derived from (meth)acrylate (salt), and continuous pores. The centrifugal retention capacity (CRC) of the absorbent material is 5–25 g / g. The bulk density is less than 0.3 g / ml, and, The neutralization rate of the crosslinked polymer is less than 70 mol%.

2. The absorbent material according to claim 1, wherein, The absorbent material has an absorption rate (Vortex) of less than 10 seconds for physiological saline based on the vortex method.

3. The absorbent material according to claim 1 or 2, wherein, The free swelling ratio (FSC) of the absorbent material is above 35 g / g.

4. The absorbent material according to any one of claims 1 to 3, wherein, The water absorption material has a water separation rate of 40% or more, as expressed by the following formula (1): Water separation rate [%] = {(FSC[g / g] - CRC[g / g]) / FSC[g / g]} × 100··(1) 5. The absorbent material according to any one of claims 1 to 4, wherein, The absorbent material contains a chelating agent.

6. The absorbent material according to any one of claims 1 to 5, wherein, The absorbent material contains inorganic microparticles.

7. A method for manufacturing a water-absorbing material, the water-absorbing material comprising an organic porous body having a continuous framework formed by a cross-linked polymer mainly composed of structural units derived from (meth)acrylate (salt) and continuous pores, the manufacturing method comprising: In the O / W emulsion preparation process, in a monomer aqueous solution with a neutralization rate of less than 70 mol%, a first solvent is encapsulated therein in the presence of a first surfactant, such that the volume ratio of the first solvent to the monomer aqueous solution is 2.5 or more, thereby obtaining an O / W emulsion. The O / W / O emulsion preparation process involves dispersing the O / W emulsion in a second solvent to obtain an O / W / O emulsion; and In the polymerization process, monomers contained in the monomer aqueous solution are polymerized in the O / W / O emulsion to prepare an organic porous body.

8. The method for manufacturing the absorbent material according to claim 7, wherein, The monomer aqueous solution contains a polymerization initiator. The polymerization initiator is an azo initiator and / or persulfate.

9. The method for manufacturing the absorbent material according to claim 7 or 8, wherein, The monomer aqueous solution contains an internal crosslinking agent. The internal crosslinking agent is selected from at least one of the group consisting of multifunctional acrylate crosslinking agents, acrylamide crosslinking agents, and glycidyl ether crosslinking agents.

10. A method for manufacturing the absorbent material according to any one of claims 7 to 9, wherein, The first surfactant is a block copolymer of polyoxyethylene-polyoxypropylene-polyoxyethylene.

11. The method for manufacturing the absorbent material according to any one of claims 7 to 10, wherein, The second solvent contains a second surfactant.

12. The method for manufacturing the absorbent material according to claim 11, wherein, The second surfactant is at least one selected from the group consisting of sucrose fatty acid esters, dehydrated sorbitol fatty acid esters, sorbitol fatty acid esters, and polyglycerol fatty acid esters.

13. The method for manufacturing the absorbent material according to any one of claims 7 to 12, wherein, The first solvent and the second solvent are of the same type.

14. A composite absorbent comprising the absorbent material according to any one of claims 1 to 6, and absorbent resin particles.

Citation Information

Patent Citations

  • Method for producing porous water-absorbing polymer particle

    JP2006342306A

  • Monolithic organic porous ion exchanger

    JP2021007900A

  • Skin barrier product with discontinuous adhesive layer

    US5051259A

  • Water-absorbent resin and production process therefor

    US7183456B2

  • Water-absorbing agent

    US7638570B2